Regulatory Framework, Public-Private Partnership Management Processes and Performance of Healthcare Projects in Kenya - Samuel Wanjema, Mwangi; Lydia Wanjiku, Gachengo; Paul K, Sang (African Journal of Education,Science and Technology (AJEST), 2025)
Healthcare projects are crucial for improving service quality and accessibility, but they frequently encounter obstacles like budget overruns, delays, and quality issues. Public-Private Partnerships (PPPs) have emerged as a potential remedy, yet their efficacy in the context of sub-Saharan Africa remains inadequately documented. This research examined the moderating effect regulatory framework on the association between PPP management practices and healthcare project performance in Kenya, with a specific focus on the Managed Equipment Services (MES) initiative, which has encountered notable cost escalations and delays. The investigation, rooted in agency theory and institutional theory, employed a mixed methods strategy within a pragmatic framework. 250 participants, representing a range of health sector stakeholders, were purposefully chosen from eight counties. Using stratified random sampling, the sample size was established at 155 respondents. A wide range of techniques, such as focus groups, interviews, and semi-structured questionnaires, were used to gather data. The analysis combined thematic insights with statistical methods, revealing that PPP management practices account for 76% of the differences in project performance. Findings also indicate that a strong regulatory environment strengthens the connection between public-private partnerships (PPPs) and successful healthcare projects (β = 0.98, p = 0.02). Based on these findings, the study recommends that organizations and project leaders develop robust regulatory frameworks to ensure PPP-driven projects thrive. Future research could explore how different project settings affect this dynamic.